Visual content and its teaching-learning process for visually impaired: a big challenge - Bine, Lailla M. S.; Svaigen, Álisson R.; Bine, Wuigor I. S.; Ruiz, Linnyer B. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2019: Anais do XXX Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2019.1251, 2019)
This work presents a survey-based study which aims to understand the experiences and difficulties between teachers and visually impaired (VI) regarding visual content and its teaching-learning process. We also exposed challenges related to assistive technologies which can aid to overcome the teaching-learning barriers. Our study shows an indicative that teachers do not believe they received a proper background to teach VIs in their formation, however, this issue has improved while they have had teaching experiences with VIs. Related to visual content, the assistive technologies which could help them are not properly disseminated. We also discussed that there are several challenges related to these technologies and their applications which remain as opened questions.